Peran Humas sebagai Pilar Reputasi: Strategi Komunikasi untuk Meningkatkan Kredibilitas Wisata Alam di Jombang - Ikhfa Amelia Tantiyuana; Afiffatur Rohimah; Abu Amar Bustomi (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the role of public relations as a key pillar in building reputation and enhancing the credibility of nature-based tourism in Jombang. The research focuses on the communication strategies employed by public relations officers in delivering information, managing public interactions, and utilizing digital media as the primary tool for strengthening destination image. The research method used is a case study with a descriptive qualitative approach. Data were collected through in-depth interviews with six informants, including public relations staff, tourism managers, representatives from the tourism department, local community members, and visitors.The findings show that public relations plays a vital role in reputation building through four main dimensions: message consistency, communication transparency, collaboration with communities and stakeholders, and the optimization of digital media. Field findings reveal that consistent use of social media strengthens tourists’ trust, while local community involvement adds authenticity to the destination’s image. Moreover, public relations also functions as a crisis communication manager by providing fast and accurate information during operational disruptions. In conclusion, the reputation of nature tourism in Jombang is not solely determined by natural beauty but also by the quality of communication managed by public relations. The optimization of digital and collaborative communication has become a key strategy to maintain the credibility and attractiveness of the destination amid increasingly competitive tourism dynamics.